Work Related Musculoskeletal Disorders in School Teachers: A Review - Patel, Niketa; Zaveri, Nidhi; Kumar, G. P. (Current Overview on Disease and Health Research Vol. 4, 2022)
Background: Musculoskeletal disorders (MSD) have become very common condition. Teaching is a profession which is not spare from MSDs. Repetitious movement, awkward postures, and high force levels are the three primary risk factors that have been associated with MSDs along with age, gender, bad posture and upset psychological levels, improper and insufficient infrastructure. The aim of this study is to present a summary review of the current state of knowledge about musculoskeletal disorders in school teachers. Methodology: The literatures were searched using various search engines and databases. Search engines were used are Google Scholar, PubMed, Science Direct and Databases are COCHRANE, CINHAL, MEDLINE, PEDRO etc. The Source of the data has been electronic sources (Databases, Electronic libraries, Electronic Journals, Google Scholar) and print sources (Journals, Textbooks, Hand searching, Follow-up reference). Results: Articles were tabulated revealing their title, author, year, study design. Conclusion: Age, gender, length of work duration, obesity, mental health and insufficient infrastructure all plays an important part in MSDs. Female teachers are more prone for developing MSDs. Frequent breaks between sessions, regular physical exercises, proper footwear, listening to owns body are the important solutions for WRMSDs in the school teachers.